The influence of risk factors for cardiovascular diseases on cardiac autonomic modulation - Rodrigues, Pedro Henrique; de Oliveira, Mariana Borges; Cazelato, Leonardo; Chagas, Eduardo Federighi Baisi; Quitério, Robison José (Journal of Health Care, 2016)
Introduction: Autonomic nervous system changes is an independent risk factor for cardiocirculatory events, which can be studied by analysis of heart rate variability (HRV). Objective: To investigate the influence of risk factors for cardiovascular disease and medications on cardiac autonomic modulation. Methods: A sample of 23 adults with at least one cardiovascular risk factor, aged 50 and 70 years. Case histories and anthropometric evaluations were conducted. In the sitting condition of rest, heart rate (HR) and RR intervals were analyzed in the time domain (HR and RMSSD), frequency (LF, HF and LF/HF), and the Poincaré plot (SD1, SD2 and SD1/SD2 ). Results: There was a correlation between the presence of a sedentary lifestyle and changes in normal levels of LF (nu) and LF/HF (R = 0.479 and R = 0.439), as well the number of risk factors and the FC (R = 0.512). Testing the influence of medications using on changes in HR and HRV was found correlation of the Angiotensin II converting enzyme inhibitors with LF (nu) and LF/HF (R = -0.505 and R = -0.550). Conclusion: A sedentary lifestyle is associated with hyperactivation of the sympathetic modulation, and a greater number of risk factors for cardiovascular disease is associated with elevated resting HR, characterizing increased stress on the cardiovascular system. But the Angiotensin II converting enzyme inhibitors is related to reductions in sympathetic modulation and sympathetic-vagal balance, which is a favorable indicator for morbidity's control.
Keywords: autonomic nervous system; risk factors; cardiovascular diseases